Real Exchange Rates and Commodity Prices - Dupont, Dominique; Juan-Ramon, V. (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the relations between fluctuations in real exchange rates among the major currencies and fluctuations in real commodity prices. Increased exchange rate volatility calls for a better understanding of these relations. To the best of our knowledge, no systematic study of those effects has been performed on a wide range of commodities, although Sjaastad and Scacciavillani (1993) have done so for gold. We build on their approach and construct a supply and demand multi-country model, with world market clearing, which incorporates speculative and non-speculative demands for inventories and 'static' and 'rational' expectations. We estimate the model using several econometric methods on monthly data from January 1972 to January 1992 for 65 commodity prices. The paper finds that, for a small group of commodities, the dollar-denominated price is significantly influenced by the deutsche mark and the yen. The empirical results show that geographical proximity matters, and that supply and demand elasticities are important in determining the commodity price in world markets above and beyond the size of the share of those commodities in world trade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet